Reações multicomponentes mediadas por catálise fotorredox - Silva, Lucas Alcantara Fernandes da (Universidade Federal de São Carlos, 2025)
This monograph presents a review of the main developments in multicomponent reactions (MCRs) mediated by photoredox catalysis, focusing on the efficient construction of organic structures with pharmaceutical and technological relevance. MCRs stand out due to their high atom economy, reaction speed, and synthetic convergence, as they combine multiple reagents in a single step. Photoredox catalysis enables the generation of reactive species through the visible-light activation of photocatalysts, allowing for highly selective and sustainable transformations. The integration of these approaches represents a promising strategy for synthesizing complex molecules under mild conditions. This review is organized according to the type of photocatalyst employed, discussing systems based on metal complexes, organic photosensitizers, and dual metal/photoredox catalysis. Proposed reaction mechanisms, representative examples from recent literature, and the potential of these methodologies in modern synthetic chemistry are discussed.
Multicomponent reactions mediated by photoredox catalysis
Keywords: Reações multicomponentes; Catálise fotorredox; Luz visível; Fotocatálise metálica; Síntese orgânica; Multicomponent reactions; Photoredox catalysis; Visible light; Metal photocatalysis; Organic synthesis; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::SINTESE ORGANICA